Acute effects of whole-body vibration on peak isometric torque, muscle twitch torque and voluntary muscle activation of the knee extensors - Jordan, M.; Norris, S.; Smith, D.; Herzog, W. (Scandinavian Journal of Medicine & Science in Sports, 2010)
The purpose of this investigation was to compare the acute effects of whole-body vibration (WBV) with a static squat on resting muscle twitch torque, peak isometric torque and voluntary muscle activation of the knee extensors during an isometric maximal voluntary contraction (MVC). Twenty-four healthy, strength-trained males were recruited for this randomized, cross-over design investigation. The WBV treatment consisted of three sets of 60 s of vibration (30 Hz, ±4 mm) while standing in a semi-squat position. Voluntary muscle activation, peak isometric torque during MVC and resting muscle twitch torque (RTT) through percutaneous femoral nerve stimulation were obtained before and following the treatment. Change in peak isometric torque, voluntary muscle activation and the RTT were calculated as the difference between pre- and post-treamtent values. There was no observable post-activation potentiation of muscle twitch torque or enhancement in voluntary muscle activation or peak isometric torque. However, decreases in the peak isometric torque (P=0.0094) and voluntary muscle activation (P=0.0252) were significantly smaller post WBV interventions compared with the control treatment. Based on the current data, it is unclear whether or not this was attributable to the effects of WBV but further research into this possibility is warranted.